2013
DOI: 10.2527/jas.2012-5873
|View full text |Cite
|
Sign up to set email alerts
|

2011 AND 2012 EARLY CAREERS ACHIEVEMENT AWARDS: Improving the production, environmental, and economic efficiency of the stocker cattle industry in the southeastern United States1,2

Abstract: Grazing forages on small-grain fields can be a profitable "second crop" for grain producers and an opportunity for cow-calf producers to retain ownership of weaned calves. The increasing costs of conventional tillage and movement of soil nutrients into surface water creates a need for more sustainable production practices to be incorporated by producers into wheat pasture production systems. Research at the Livestock and Forestry Research Station near Batesville, AR, and the Southwest Research and Extension Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…The cool-season annuals averaged (DM basis) 25.0 ± 2.1% CP, 29.2 ± 2.8% ADF, 48.6 ± 3.7% NDF, and 69.8 ± 3.2% TDN during the spring. The composition of the cool-season annual pastures in the current experiment is similar to that reported in an overview of 6 experiments by Beck et al (2013) and was able to provide supplemental nutrients to cows during the critical calving and early lactation periods in the late winter and early spring. Cows in MR pastures were fed very little hay during the first 2 yr of the experiment and were maintained primarily on strip-grazed stockpiled bermudagrass, whereas cows in HR grazed stockpiled bermudagrass much later into the winter than was the original intent.…”
Section: Forage Mass and Nutritive Qualitysupporting
confidence: 68%
“…The cool-season annuals averaged (DM basis) 25.0 ± 2.1% CP, 29.2 ± 2.8% ADF, 48.6 ± 3.7% NDF, and 69.8 ± 3.2% TDN during the spring. The composition of the cool-season annual pastures in the current experiment is similar to that reported in an overview of 6 experiments by Beck et al (2013) and was able to provide supplemental nutrients to cows during the critical calving and early lactation periods in the late winter and early spring. Cows in MR pastures were fed very little hay during the first 2 yr of the experiment and were maintained primarily on strip-grazed stockpiled bermudagrass, whereas cows in HR grazed stockpiled bermudagrass much later into the winter than was the original intent.…”
Section: Forage Mass and Nutritive Qualitysupporting
confidence: 68%
“…Animal supplementation on native grasslands allows nutrient input to increase, having a positive effect on ADG (Boval et al, 2015). In fact, Beck et al (2013) carried out a literature review in which low quality forages were considered, and they concluded that supplementation on warm season forages significantly increased ADG compared to non-supplemented schemes. In the current study, both experiments registered a positive effect of supplementation on ADG, when comparing treatments with restricted supplementation rates (E and RSF; Table 3 and Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…For each year, grazing was initiated once available forage DM was estimated to be above 1785 lb/acre. Grazing was terminated when steer ADG fell below 1 lb/day or available forage DM was estimated to be <1000 lb/acre (approximate amount of available forage DM required to support steer ADG of 1 lb/day at the stocking rate utilized in this study [Beck et al, 2013]). Steers were provided free-choice mineral mix containing lasalocid (VMS Kowpoke 4 B1200, Ridley Block Operations, Mankato, MN) and water ad libitum throughout this study.…”
Section: Location Establishment Data Collection and Analysismentioning
confidence: 99%